2015
DOI: 10.5897/jssem2013.0406
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation, phosphorous and zinc fertilization effects on nodulation, yield and nutrient uptake of Faba bean (Vicia faba L.) grown on calcaric cambisol of semiarid Ethiopia

Abstract: A field experiment was conducted in 2010 crop season with three factors: Inoculation (U = no inoculums and I = with inoculums), three levels of P (0, 20, 40kgPha-1) and three levels of Zn (0, 15, 25kgZnha-1) fertilizations. The experiments were laid in randomized complete blocks in three replications on calcaric cambisols to study effects of inoculation, P and Zn fertilizations on nodulation, yield, yield components, and the uptake N, P and Zn by the plant. Composite soil samples were collected one month befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Zn is involved in auxin metabolism like, tryptophane synthesis, tryptamine metabolism, protein synthesis, formation of nucleic acid and helps in utilization of nitrogen as well as phosphorus by plants (Ram and Katiyar, 2013). Similar to the current findings N uptake increase due to rhizobium inoculation, S and Zn application have been reported by several literatures (Abdalla et al, 2011;Das et al, 2016;Desta et al, 2015;El-kade and Mona, 2013;Hussain et al, 2011;Islam et al, 2013;Jay et al, 2012;Kesare, 2014;Mondal et al, 2005;Najar et al, 2011;Rokhzadi and Toashih, 2011;Shamima and Farid, 2006;Srinivasulu et al, 2015;Srivastava et al, 2006;Togay et al, 2008;Zaidi et al, 2003;Zerihun et al, 2017) Total phosphorus uptake…”
Section: Total Nitrogen Uptakesupporting
confidence: 93%
“…Zn is involved in auxin metabolism like, tryptophane synthesis, tryptamine metabolism, protein synthesis, formation of nucleic acid and helps in utilization of nitrogen as well as phosphorus by plants (Ram and Katiyar, 2013). Similar to the current findings N uptake increase due to rhizobium inoculation, S and Zn application have been reported by several literatures (Abdalla et al, 2011;Das et al, 2016;Desta et al, 2015;El-kade and Mona, 2013;Hussain et al, 2011;Islam et al, 2013;Jay et al, 2012;Kesare, 2014;Mondal et al, 2005;Najar et al, 2011;Rokhzadi and Toashih, 2011;Shamima and Farid, 2006;Srinivasulu et al, 2015;Srivastava et al, 2006;Togay et al, 2008;Zaidi et al, 2003;Zerihun et al, 2017) Total phosphorus uptake…”
Section: Total Nitrogen Uptakesupporting
confidence: 93%
“…Makoi et al (2013) revealed improvement in the uptake of N and P following inoculation of different legumes with effective strains of rhizobia. Nyoki and Ndakidemi (2014) found that Bradyrhizobium japonicum inoculation complemented with phosphorus application in cowpea enhanced the uptake of nutrients such as N and P. Similarly, Desta et al (2015) indicated that the inoculation of legume crops can improve nodulation capacity and nitrogen fixation, which, in turn, enhance nutrient uptake of fava bean.…”
Section: Nutrient Availability and Uptakementioning
confidence: 97%
“…Phosphorus is also critical for both establishments of nodulation and N 2 fixation. Poor nodulation and poor plant vigor are observed in legumes grown in soils low in extractable phosphorus (Desta et al, 2015;Wolde-meskel et al, 2018). Uchida (2000) revealed that phosphorus is vital in several key plant functions, including photosynthesis, transfer of energy, conversion of sugars and starches, movement of nutrients within the plant, and transmission of genetic traits from one generation to the next.…”
Section: The Use Of Appropriate Agronomic Practices and Cropping Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kang and van Iersel (2004) reported Leaf area ratio increased with increasing fertilizer concentration. Similarly, Weldua et al (2012) and Namakka et al (2017) while working on the effect of Zn and phosphorus application on yield at yield component of Faba bean (Vicia faba L.), and effect of phosphorus levels on cowpea reported that higher levels of P at 40 and 60 kgha -1 , and 29 and 39 kgPha -1 had higher (P<0.05) LAR than lower levels of 0 and 20, and 0 and 10 kgha -1 respectively. Increment of LAR due phosphorus application may be attributed to the activation of metabolic processes, where P is important nutrient that increases the leaf area ratio and improve the rate of photosynthetic assimilate (Yemane and Skjeivg, 2003) and (Mohammed et al, 2022).…”
Section: Effects Of Year Phosphorus Zinc and Interactions On Lai Of D...mentioning
confidence: 92%